(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2023)
This paper is the result of an exploratory research about Mapuche women’s writings between 1935 and 1965 available in Mapuche newspapers, as well as in educational institutions and journals of social movements. The goals of this research are to review the historical elements that allow the emergence of the women’s prose, and to break down the central aspects of these writings, specifically, the relationship with civil rights, the demand for education and the fight against racism. The article arises from a study carried out in press archives in the National Library of Chile and documents in the Gabriela Mistral Museum of Education, as well as brief research in the Regional Archive of Araucanía.